Kebijakan Pemerintah dalam Menangani Dinamika Subsidensi Tanah di Tambakrejo Semarang - Atha Difa Saputri; Angel Maris Linda (CV Rewang Rencang, 2023)
Land subsidence that occurs in Tambakrejo Semarang has decreased by 10 to 13 cm each year. However, no effective policy has been implemented by the Government. The aim of this journal is to find out how many government policy steps have been taken to cope with land subsidence in Tambakrejo, Semarang. The method of the journal empirical juridical method which researchers make observations, collect facts through interviews with sources and collect data from various journals. The results obtained, the impact of Tambakrejo on losses from the subsidence of material and immaterial losses.The Government-implemented policies, are less effective for Tambakrejo Semarang.